SERPUKHOVIAN AND EARLY BASHKIRIAN (CARBONIFEROUS) NAUTILOIDS (CEPHALOPODA) OF THE DONETS BASIN (UKRAINE) - Дернов, В.С. (Institute of Geological Sciences, NAS of Ukraine, 2025)
Serpukhovian (?Pseudorthoceras spp., Gzheloceras aisenvergi Dernov, 2021, G. sp., and Catastrobocerassp.) and early Bashkirian (Orthocerida indet., Pseudogzheloceras spp., Millkoninckiocerasudovichenkoi Dernov, 2018, Catastroboceras sp., and Imonautilus sp.) nautiloid assemblagesare described from the Samara, Kalmius, Amvrosiyivka, and Mandrykyne formations(Prokhorivskian-Blagodatnean horizons) of the Donets Basin, eastern Ukraine. These low-diverseassociations are quite similar in systematic composition to the Serpukhovian and Bashkiriannautiloid assemblages of Western Europe and North America.